The System-Supplementing Effect of the Interaction between Innovative Capacity and Institutional Environment Factors of a Region - Ovchinnikov, Viktor Nikolayevich; Ketova, Natalya Petrovna (Economy of Regions, 2016)
In the article, the effect of interaction between the development level of regional innovative capacity and its innovative and institutional infrastructure is traced. The research objective is to prove the hypothesis of the essential impact of the regional institutional and information environment on its innovative capacity, the identification of the effect of their system-supplementing interaction. From the standpoint of the methodology of system-structural research its components are allocated within the innovative capacity of the regional innovative system (RIS), they are presented by a corporate sector, the structures of small and medium business, and also by the subjects of ethnic economy. The use of essential-analytical and functional approaches has revealed the leading role of intangible assets of the corporate sector of the economy in region’s innovative development. The correlation and regression analysis has confirmed the essential dependence of the innovative activity of the region on the systemic completeness of the development of its institutional and infrastructure environment. The results of the research have shown that to ensure the system-supplementing effect of the interaction between innovative capacity and the factors of its activation in the sphere of institutional infrastructure, it is necessary to consistently develop its operational base - the institutions of RIS. The recommendations reasoned in the article may be used for the development of regional innovation strategies, the formation of innovation clusters. The three-component structure of the innovation cluster of the region is offered; its integrating function in relation to the innovative components of the regional sectoral clusters is determined. The factors constraining the growth of innovation activity of the regional economic subjects are revealed and the recommendations on the development of the institutional and infrastructural environment of the Rostov region are substantiated.